Large-scale in-silico identification of a tumor-specific antigen pool for targeted immunotherapy in triple-negative breast cancer - Kaufmann, Jessica; Wentzensen, Nicolas; Brinker, Titus Josef; Grabe, Niels (OncoTarget, 2019)
https://doi.org/10.18632/oncotarget.26808 Jessica Kaufmann, Nicolas Wentzensen, Titus J. Brinker, Niels Grabe